Method for preparing bio-based adhesive by using eucalyptus bark and sugar cane pith and application thereof
Patent Information
- Application Number
- CN202610756802.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-09-04
AI Technical Summary
[0007]本发明的一个目的是提供一种以桉树皮和蔗髓为有机原料、不使用苯酚和甲醛的胶粘剂基本制备方法,通过液化、羧甲基化改性及环氧大豆油交联的组合,解决现有技术中原料有毒、产品含醛的问题
1、本发明以桉树皮和蔗髓为有机原料,完全替代苯酚和甲醛。桉树皮经多元醇液化后得到富含羟基的低聚物,蔗髓经羧甲基化改性后引入羧甲基活性基团。两者在环氧大豆油存在下,环氧基与羟基、羧甲基发生开环交联反应,形成三维网络结构,无需甲醛参与。经测试,实施例1至3的胶粘剂甲醛释放量均未检出(检测限小于0.1 mg/L),实现了无醛化目标。同时,桉树皮(通常作为废弃物燃烧或填埋)和蔗髓(制糖副产物)得到利用,降低了胶粘剂对化石原料的依赖。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of adhesives and engineered wood products technology, specifically relating to a method for preparing bio-based adhesives using eucalyptus bark and sugarcane pith, and the application of the obtained bio-based adhesives in the preparation of bamboo-wood composite boards. Background Technology
[0002] Utilizing eucalyptus processing residues and bagasse residues to produce fiberboard, particleboard, and other engineered wood products is an important way to achieve resource recovery. However, the following problems still exist in existing technologies and have not been effectively solved.
[0003] Eucalyptus wood, due to its porous texture and high growth stress, is prone to warping and deformation during drying and use when used alone. Combining bamboo with eucalyptus wood utilizes the high tensile strength and dimensional stability of bamboo to restrain the deformation of eucalyptus, thus improving the dimensional stability of the boards to some extent.
[0004] Aldehyde-based adhesives are widely used in the wood adhesive industry, and their products continuously release formaldehyde during their service life. In Chinese patent publication CN111961429B, Zhang Yifu et al. from Guangxi University disclosed a method for preparing a eucalyptus bark powder-modified phenolic resin wood adhesive. This method uses eucalyptus bark powder as a partial substitute for phenol and polycondenses it with formaldehyde. Although this reduces the cost of the adhesive, formaldehyde release still exists in the product. Existing technical literature (Fu Yunlin, Mo Yinyou, Qin Guanli, et al. Liquefaction of Eucalyptus Bark and Resinization of Liquefied Products [J]. Journal of Zhejiang A&F University, 2011, 28(3): 466-471) reported on the liquefaction of phenol in eucalyptus bark and the resinization of liquefied products. The liquefaction of eucalyptus bark was carried out using phenol as a liquefying agent and concentrated sulfuric acid as a catalyst. The liquefaction was then carried out with formaldehyde to prepare an adhesive. The average bonding strength was 0.8358 MPa, but the formaldehyde release was 1.5 mg / L, which belongs to the E2 level.
[0005] In terms of resource utilization, eucalyptus bark is usually burned or landfilled as waste in existing eucalyptus processing, failing to achieve high-value utilization. Research on sugarcane pith (the pith tissue screened from bagasse) in the adhesive field is extremely limited. Existing reports (Wu Maochang. Preparation and performance study of novel molded packaging materials using sugarcane pith [J]. Packaging Engineering, 2009, 30(04):34-36) mostly use it as an inert filler in molded packaging materials, or use acid pulping waste liquor as an adhesive for physical bonding. No research has been found on converting sugarcane pith into an active component of adhesives through chemical modification. Sugarcane pith is rich in cellulose and hemicellulose, possessing certain reactivity, but current technologies have failed to effectively utilize it in formaldehyde-free adhesives. The liquefaction treatment of bark largely relies on phenol and formaldehyde systems, lacking exploration of completely formaldehyde-free systems.
[0006] In summary, existing technologies lack a complete technical solution for preparing high-performance bio-based adhesives using eucalyptus bark and sugarcane pith as organic raw materials without the use of phenol and formaldehyde. Furthermore, there are no reports on systematically matching the interfacial properties of the adhesive with bamboo-wood composite panels. Therefore, developing a bio-based adhesive that achieves both high-value utilization of eucalyptus bark and sugarcane pith while meeting formaldehyde-free environmental requirements, and its application method in bamboo-wood composite panels, is of significant practical importance. Summary of the Invention
[0007] One objective of this invention is to provide a basic preparation method for adhesives using eucalyptus bark and sugarcane pith as organic raw materials without the use of phenol and formaldehyde. This method solves the problems of toxic raw materials and aldehyde-containing products in the prior art through a combination of liquefaction, carboxymethylation modification, and crosslinking with epoxidized soybean oil.
[0008] To achieve the above objectives, the present invention provides a method for preparing a bio-based adhesive using eucalyptus bark and sugarcane pith, comprising the following steps: Step 1: Mix dried and pulverized eucalyptus bark with polyol solvent and acidic catalyst, and react at 140℃~180℃ for 1~3 hours. After cooling, eucalyptus bark liquefaction polyol resin is obtained. Step 2: Mix the dried and pulverized sugarcane pith with sodium hydroxide aqueous solution and chloroacetic acid, and react at 50℃~70℃ for 1~3 hours. After neutralization, washing and drying, carboxymethylated modified sugarcane pith is obtained. Step 3: By weight, take 40-80 parts of the eucalyptus bark liquefied polyol resin obtained in Step 1, 10-30 parts of the carboxymethylated modified sugarcane pith obtained in Step 2, 5-20 parts of epoxidized soybean oil, and 5-20 parts of water, and mix them evenly. Step 4: Adjust the pH of the mixture obtained in Step 3 to 7.5-9.0 with an alkaline substance to obtain the bio-based adhesive.
[0009] Preferably, the polyol solvent in step one is a mixture of polyethylene glycol and glycerol, wherein the mass ratio of polyethylene glycol to glycerol is 3.5:1 to 4.5:1, and the average molecular weight of polyethylene glycol is 300 to 600; the acidic catalyst is p-toluenesulfonic acid, and the amount used is 1% to 4% of the mass of the polyol solvent; the reaction temperature is 170°C, and the time is 2.0 to 2.5 hours; the cooling is a programmed cooling: first, the temperature is reduced from 170°C to 100°C at a rate of 1 to 3°C / min, and then the temperature is reduced from 100°C to room temperature at a rate of 3 to 5°C / min.
[0010] Preferably, before step one, the eucalyptus bark is pretreated as follows: the eucalyptus bark is dried at 60℃~80℃ to a moisture content of 3%~8%, pulverized to 60~100 mesh, then extracted by reflux extraction with a benzene-ethanol mixed solvent at 65℃~75℃ for 2~4 hours, filtered, and the filter residue is dried again at 60℃~80℃ to constant weight, and finally pulverized to pass through an 80~200 mesh sieve to obtain the dried and pulverized eucalyptus bark.
[0011] Preferably, in step two, the mass ratio of the dried and pulverized sugarcane pith, sodium hydroxide, and chloroacetic acid is 100:5-15:10-20; the neutralization is achieved by adjusting the pH to 6.5-7.0 with dilute hydrochloric acid or dilute sulfuric acid; the washing is performed by washing 2-4 times with deionized water or ethanol; and the drying is performed by vacuum drying at 50℃-70℃ to constant weight.
[0012] Preferably, the epoxy value of the epoxidized soybean oil in step three is 6.0% to 7.0%.
[0013] Preferably, the alkaline substance in step four is an aqueous solution of sodium hydroxide or an aqueous solution of sodium carbonate, with a mass concentration of 5% to 20%.
[0014] Preferably, after step one, a stabilization treatment is further included: adding 0.5% to 2% by mass of calcium carbonate powder, wherein the calcium carbonate powder is nano-calcium carbonate with an average particle size of 50 to 200 nm, and mixing the calcium carbonate powder with glycerol at a mass ratio of 1:0.5 to 1:2, and then grinding it in a ball mill at 200 to 400 r / min for 30 to 60 minutes to make a slurry before adding it; stirring at 40°C to 50°C for 30 to 60 minutes, and then filtering to remove solid residue, to obtain stabilized eucalyptus bark liquefied polyol resin.
[0015] The present invention provides the application of a bio-based adhesive prepared by any of the methods described herein in the preparation of bamboo-wood composite boards, comprising the following steps: Step A: Prepare a bamboo surface pretreatment agent, which is a mixed aqueous dispersion of carboxymethylated sucrose pith and glycerol, wherein the mass concentration of carboxymethylated sucrose pith is 2% to 5% and the mass concentration of glycerol is 5% to 10%, and the pH is adjusted to 8.0 to 9.0 with sodium hydroxide; Step B: Impregnate or spray the surface of the bamboo reinforcement layer to be glued with the pretreatment agent, and dry it at 60℃~80℃ for 3~5 minutes to form a carboxymethylated sucrose pith coating on the bamboo surface, thus obtaining the pretreated bamboo reinforcement layer. Step C: Prepare a eucalyptus surface sealant, wherein the sealant is a diluted solution of any of the bio-based adhesive stock solutions and ethanol at a volume ratio of 1:0.5 to 1:1; Step D: Spray the sealant onto the upper and lower surfaces of the eucalyptus fiber core layer, with a spraying amount of 20-40 g / m². 2 The ethanol will evaporate naturally in 2-4 minutes; Step E: Prepare a bio-based adhesive stock solution using any one of the methods described above, and set aside for later use; Step F: Apply the bio-based adhesive concentrate to the pretreated bamboo reinforcement layer and the upper and lower surfaces of the sealed eucalyptus fiber core layer, with a single-sided application rate of 120-150 g / m². 2 ; Step G: Assemble the blanks in the order of eucalyptus fiber core layer in the middle and bamboo reinforcement layer on both sides to form a board blank; Step H: Place the slab in a hot press and hot press it for 8 to 12 minutes at 130℃~150℃ and 1.2~1.8MPa. After cooling, the bamboo-wood composite board is obtained.
[0016] Preferably, after the hot pressing in step H is completed, the pressure is maintained to cool the slab to 60°C to 80°C at a cooling rate of 3°C / min to 8°C / min, and then the pressure is released and the slab is removed.
[0017] Preferably, the pretreatment agent in step A further contains 0.1% to 0.5% by weight of carboxymethylated sugarcane pith, of 2-ethyl-4-methylimidazole.
[0018] The beneficial effects of this invention are as follows: 1. This invention uses eucalyptus bark and sugarcane pith as organic raw materials, completely replacing phenol and formaldehyde. Eucalyptus bark is liquefied with polyols to obtain oligomers rich in hydroxyl groups, while sugarcane pith is modified by carboxymethylation to introduce carboxymethyl active groups. In the presence of epoxidized soybean oil, the epoxy groups react with the hydroxyl and carboxymethyl groups to form a ring-opening crosslinking reaction, forming a three-dimensional network structure without the need for formaldehyde. Testing showed that the formaldehyde release of the adhesives in Examples 1 to 3 was undetectable (detection limit less than 0.1 mg / L), achieving the goal of formaldehyde-free production. Simultaneously, eucalyptus bark (usually burned or landfilled as waste) and sugarcane pith (a sugar refining byproduct) are utilized, reducing the adhesive's dependence on fossil fuels.
[0019] 2. Compared with existing technologies (phenol-formaldehyde system), the adhesive prepared in this invention exhibits higher bonding strength in poplar plywood. The wet bonding strength of Example 1 is 1.13 MPa, which is about 34% higher than that of Comparative Example 1 (0.84 MPa). This is because the hydroxyl groups in the liquefied polyol resin of eucalyptus bark form a cross-linking network with the epoxy groups of epoxidized soybean oil. At the same time, the carboxymethylated modified sugarcane pith participates in network construction as an active cross-linking component (carboxymethyl and epoxy ring-opening esterification) and also provides physical reinforcement as a fibrous filler. The two work synergistically to improve the cohesive strength and water resistance of the adhesive layer. The bonding strength of Comparative Example 2 (without modified sugarcane pith) is only 0.51 MPa, and the bonding strength of Comparative Example 3 (without modified sugarcane pith) is 0.58 MPa, confirming the necessity of carboxymethylation modification.
[0020] 3. Untreated eucalyptus bark liquefied resin contained residual p-toluenesulfonic acid. After 90 days of storage at room temperature, the acid value increased from 11.2 mgKOH / g to 20.1 mgKOH / g, the viscosity increased from 1050 mPa·s to 2850 mPa·s, and the bonding strength decreased significantly. By adding nano-calcium carbonate (pre-ball-milled with glycerol to form a slurry) to the liquefied resin, neutralizing the residual acid, and removing it by filtration, the resin's acid value decreased to 1.8 mgKOH / g. After 90 days of storage, the acid value only increased to 2.3 mgKOH / g, the viscosity increased to 1180 mPa·s, and the bonding strength still reached 1.08 MPa. This indicates that the removal of residual acid effectively inhibited the esterification and etherification side reactions during storage, extending the resin's shelf life.
[0021] 4. In the preparation of bamboo-wood composite panels, the bamboo-wood interface bonding strength of Panel-11 without any interface treatment was only 0.47 MPa, with a thickness resilience of 7.0%. By pre-coating the bamboo surface with a carboxymethylated sucrose pith pretreatment agent (forming a porous hydrophilic coating) and pre-coating the eucalyptus surface with an adhesive stock solution-ethanol sealant (partially sealing the pores), the bamboo-wood interface bonding strength of Panel-5 increased to 1.17 MPa, which is basically the same as the wood-wood interface strength (1.20 MPa), while the thickness resilience decreased to 2.2%. The carboxymethylated sucrose pith coating on the bamboo surface provides a large number of carboxymethyl and hydroxyl groups, forming chemical bonds with the subsequently applied adhesive; the sealing layer on the eucalyptus surface slows down the excessive penetration of the adhesive into the wood interior, making the interface adhesive distribution more uniform. The bonding strengths of Comparative Examples 12 (bamboo pretreatment only) and 13 (eucalyptus sealing only) were 0.84 MPa and 0.61 MPa, respectively, confirming the synergistic effect of the two.
[0022] 5. The panel-14 bamboo-wood interface bonding strength was 0.95 MPa and the thickness resilience was 4.6% when the pressure was immediately released after hot pressing; while the corresponding values for panel-5, which was cooled to 70℃ while maintaining pressure, were 1.17 MPa and 2.2%. Pressure holding and cooling allowed the adhesive layer to continue to cure under pressure. When the temperature dropped to 60-80℃, the degree of cross-linking was sufficient to resist the resilience stress of the bamboo, thereby reducing interface damage.
[0023] 6. After adding 0.3% 2-ethyl-4-methylimidazol to the bamboo pretreatment agent, the bonding strength of the bamboo-wood interface of Panel-5-P was further increased to 1.31 MPa, and the thickness resilience was reduced to 1.6%. This accelerator catalyzes the ring-opening reaction of carboxymethyl and epoxy groups in the early stage of hot pressing (above 100℃), enabling the bamboo-adhesive interface to form a high-strength anchoring layer in advance, which more effectively resists the rebound stress, while not affecting the pot life of the adhesive matrix.
[0024] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Detailed Implementation
[0025] The present invention will be further described in detail below with reference to examples, so that those skilled in the art can implement it based on the description. It should be noted that, unless otherwise specified, the experimental methods in the following embodiments are conventional methods, and the reagents and materials are commercially available unless otherwise specified.
[0026] Example 1 This invention discloses a method for preparing a bio-based adhesive using eucalyptus bark and sugarcane pith, comprising: Pretreatment of eucalyptus bark: After removing impurities from the bark of *Eucalyptus globulus*, it was dried in a forced-air drying oven at 70℃ until the moisture content was 5%. After removal, it was pulverized using a pulverizer and passed through an 80-mesh sieve to obtain coarse eucalyptus bark powder. 100g of the above coarse eucalyptus bark powder was placed in a Soxhlet extractor and extracted by reflux at 70℃ for 3 hours with a benzene-ethanol mixed solvent (volume ratio 2:1). After extraction, the residue was filtered and collected, then dried in a vacuum drying oven at 60℃ until constant weight. The dried residue was further pulverized using an ultrafine pulverizer and passed through a 120-mesh sieve to obtain pretreated eucalyptus bark powder for later use.
[0027] Preparation of eucalyptus bark liquefied polyol resin: 300g of a mixed solvent of polyethylene glycol 400 (PEG-400) and glycerol (PEG-400 to glycerol mass ratio 4:1) was added to a 500mL four-necked flask; 6g of p-toluenesulfonic acid (2.0% of the polyol solvent mass) was added and stirred to dissolve. 100g of the pretreated eucalyptus bark powder was added, and the mixture was heated to 170℃ at a rate of 5℃ / min under mechanical stirring and reacted at this temperature for 2.5 hours. After the reaction was completed, the reaction mixture was first cooled from 170℃ to 100℃ at a rate of 2℃ / min, and then cooled from 100℃ to room temperature at a rate of 4℃ / min to obtain the eucalyptus bark liquefied polyol resin, denoted as A-1.
[0028] Preparation of carboxymethylated modified sugarcane pith: Take 100g of dried and pulverized sugarcane pith (moisture content ≤3%, particle size 80 mesh), add it to a 500mL three-necked flask, add 50g of 20% sodium hydroxide aqueous solution (i.e., 10g of NaOH oven-dry weight), 15g of chloroacetic acid, and 150g of deionized water, and stir well. Heat to 60℃ and react at a constant temperature for 2 hours. After the reaction is complete, adjust the pH to 6.5~7.0 with dilute hydrochloric acid, filter, wash 3 times with deionized water, and dry the filter cake in a vacuum drying oven at 60℃ to constant weight to obtain carboxymethylated modified sugarcane pith, denoted as C-1.
[0029] Adhesive compounding: Take 60 parts by weight of A-1, 20 parts by weight of C-1, 10 parts by weight of epoxidized soybean oil (epoxidation value 6.5%), and 10 parts by weight of deionized water. Place them in a high-speed disperser and stir at 800 r / min for 15 minutes until homogeneous. Adjust the pH of the mixture to 8.0 with a 10% sodium hydroxide aqueous solution to obtain the bio-based adhesive, denoted as G-1.
[0030] Example 2 Pretreatment of eucalyptus bark raw material: The eucalyptus bark was dried at 75℃ to a moisture content of 6%, pulverized and passed through a 100-mesh sieve, and then extracted (benzene-ethanol volume ratio 2:1, reflux extraction at 72℃ for 2.5 hours). The filter residue was vacuum dried at 60℃ and then pulverized and passed through a 150-mesh sieve. The remaining operations were the same as in Example 1.
[0031] Preparation of eucalyptus bark liquefied polyol resin: The mass ratio of PEG-400 to glycerol was 3.8:1, the amount of p-toluenesulfonic acid was 1.5% of the mass of the polyol solvent, the liquefaction temperature was 165℃, and the liquefaction time was 2.2 hours. Cooling: First, the temperature was reduced from 165℃ to 100℃ at a rate of 1.5℃ / min, and then reduced from 100℃ to room temperature at a rate of 3.5℃ / min. The remaining operations were the same as in Example 1, and the resulting liquefied resin was designated A-2.
[0032] Preparation of carboxymethylated modified sugarcane pith: 100g of dried and pulverized sugarcane pith, 40g of a 20% sodium hydroxide aqueous solution (8g of NaOH at oven-dry weight), 12g of chloroacetic acid, and 150g of deionized water were added, and the mixture was reacted at a constant temperature of 55℃ for 2.5 hours. After neutralization and washing, it was dried under vacuum at 65℃. The rest of the process was the same as in Example 1, and the resulting modified sugarcane pith was designated C-2.
[0033] Adhesive compounding: 70 parts A-2, 15 parts C-2, 15 parts epoxidized soybean oil (epoxidation value 6.2%), and 10 parts deionized water are dispersed at high speed for 20 minutes. The pH is adjusted to 8.2 with sodium carbonate aqueous solution (mass concentration 10%) to obtain bio-based adhesive G-2.
[0034] Example 3 Pretreatment of eucalyptus bark raw material: The eucalyptus bark was dried at 65℃ to a moisture content of 4%, pulverized and passed through a 60-mesh sieve, and then extracted (benzene-ethanol volume ratio 2:1, reflux extraction at 68℃ for 4 hours). The filter residue was vacuum dried at 60℃ and then pulverized and passed through a 180-mesh sieve. The remaining operations were the same as in Example 1.
[0035] Preparation of eucalyptus bark liquefied polyol resin: The mass ratio of PEG-400 to glycerol was 4.2:1, the amount of p-toluenesulfonic acid was 3.0% of the polyol solvent mass, the liquefaction temperature was 175℃, and the liquefaction time was 2.0 hours. Cooling: First, the temperature was reduced from 175℃ to 100℃ at a rate of 2.5℃ / min, and then reduced from 100℃ to room temperature at a rate of 4.5℃ / min. The remaining operations were the same as in Example 1, and the resulting liquefied resin was designated A-3.
[0036] Preparation of carboxymethylated modified sugarcane pith: 100g of dried and pulverized sugarcane pith, 48g of a 25% sodium hydroxide aqueous solution (12g of NaOH at oven-dry weight), 18g of chloroacetic acid, and 150g of deionized water were added, and the mixture was reacted at a constant temperature of 65℃ for 2 hours. After neutralization and washing, it was vacuum dried at 55℃. The rest was the same as in Example 1, and the resulting modified sugarcane pith was designated C-3.
[0037] Adhesive compounding: 50 parts A-3, 25 parts C-3, 12 parts epoxidized soybean oil (epoxidation value 6.8%), and 13 parts deionized water are dispersed at high speed for 25 minutes. The pH is adjusted to 7.8 with sodium hydroxide aqueous solution (mass concentration 8%) to obtain bio-based adhesive G-3.
[0038] Comparative Example 1: Eucalyptus bark phenol liquefaction / formaldehyde condensation adhesive This comparative example was prepared according to the method for preparing phenol liquefaction and formaldehyde condensation adhesive for eucalyptus bark disclosed in the existing technical literature (Fu Yunlin, Mo Yinyou, Qin Guanli, Zhao Lin, Rong Yuquan. Liquefaction of eucalyptus bark and resinification of liquefied products [J]. Journal of Zhejiang A&F University, 2011, 28(3): 466-471).
[0039] Eucalyptus bark raw material: After removing impurities from the bark of the blue gum tree, it is dried at 60℃ to a moisture content of about 10%, crushed, and then passed through a 100-mesh sieve. No extraction or removal pretreatment is performed.
[0040] Eucalyptus bark phenol liquefaction: 300g of phenol and 18g of 36% sulfuric acid (6% of the total liquefied product) were added to a 500mL four-necked flask and stirred until homogeneous. 90g of dried and pulverized eucalyptus bark powder (liquid-to-solid mass ratio 10:3) was added, and the mixture was heated to 150℃ with stirring and reacted at this temperature for 80 minutes. After the reaction was complete, the reaction mixture was allowed to cool naturally to room temperature to obtain the eucalyptus bark phenol liquefaction product, denoted as D-1.
[0041] Formaldehyde condensation resinification: Take 100g of the above D-1, add 44g of 37% formaldehyde aqueous solution (formaldehyde molar ratio 1.6), 16g of 40% sodium hydroxide solution (NaOH molar ratio 0.3), and 24g of deionized water (water molar ratio 8.0), and stir until homogeneous. Heat to 95℃ and maintain the reaction temperature for 1.5 hours. Cool to 40℃ and discharge to obtain phenolic resin adhesive, denoted as D-2.
[0042] Comparative Example 2: Control adhesive made with polyol liquefaction but without modified sugarcane pith Eucalyptus bark raw material: Same as in Example 1, but without extraction and removal pretreatment (i.e., only drying and pulverizing, without benzene-ethanol reflux extraction).
[0043] Preparation of eucalyptus bark liquefied polyol resin: A PEG-400 / glycerol mixed solvent (mass ratio 4:1) was used, with p-toluenesulfonic acid accounting for 3% of the polyol solvent mass. The liquefaction temperature was 160°C, and the liquefaction time was 3 hours. The resin was then allowed to cool naturally to room temperature. The remaining operations were the same as in Example 1. The resulting liquefied resin was designated as E-1.
[0044] Adhesive formulation: Take 70 parts of E-1, 20 parts of epoxidized soybean oil (epoxidation value 6.5%), and 10 parts of deionized water, mix and stir evenly, adjust the pH to 8.0, and the adhesive is obtained, denoted as E-2. This comparative example does not contain carboxymethylated modified sucrose pith.
[0045] Comparative Example 3: Control adhesive using unmodified sugarcane pith instead of carboxymethylated sugarcane pith Preparation of eucalyptus bark liquefied polyol resin: Same as comparative example 2, the liquefied resin is denoted as F-1.
[0046] Preparation of unmodified sugarcane pith: The dried and pulverized sugarcane pith (same as in Example 1, particle size 80 mesh) was used directly without carboxymethylation modification and was designated as F-2.
[0047] Adhesive compounding: Take 60 parts of F-1, 20 parts of F-2, 10 parts of epoxidized soybean oil (epoxidation value 6.5%), and 10 parts of deionized water, mix and stir evenly, adjust the pH to 8.0, and the adhesive is obtained, which is denoted as F-3.
[0048] Comparative Example 4: Different liquefaction temperatures and times Pretreatment of eucalyptus bark raw materials: Same as in Example 1.
[0049] Preparation of eucalyptus bark liquefied polyol resin: The mass ratio of PEG-400 to glycerol was 4:1, the amount of p-toluenesulfonic acid was 2.0% of the mass of the polyol solvent, the liquefaction temperature was 130℃ (below the lower limit of 140℃), and the liquefaction time was 3.5 hours. Cooling: A single-stage natural cooling process was used to room temperature (no programmed cooling). The remaining operations were the same as in Example 1, and the resulting liquefied resin was denoted as L-4.
[0050] Adhesive formulation: Same as in Example 1 (L-4 60 parts, C-1 20 parts, epoxidized soybean oil 10 parts, water 10 parts, pH 8.0), adhesive is designated as G-4c.
[0051] Comparative Example 5: Preparation of liquefied polyol resin by replacing eucalyptus bark with sugarcane bagasse powder This comparative example uses sugarcane bagasse powder as raw material to prepare liquefied polyol resin, and then blends it with carboxymethylated modified sugarcane pith and epoxidized soybean oil of the present invention to verify the effect of eucalyptus bark raw material in the present invention.
[0052] Raw material: Sugarcane bagasse (the residue after removing the pith) is dried and pulverized to pass through a 100-mesh sieve, with a moisture content of ≤5%. No extraction or removal pretreatment is performed.
[0053] Preparation of sugarcane bagasse liquefaction polyol resin: 300 g of a mixed solvent of PEG-400 and glycerol (mass ratio 4:1) was added to a 500 mL four-necked flask, along with 6 g of p-toluenesulfonic acid, and stirred until dissolved. 100 g of sugarcane bagasse powder was added, and the mixture was heated to 160 °C at a rate of 5 °C / min under mechanical stirring, and reacted at this temperature for 3 hours. Cooling: Allow to cool naturally to room temperature. The resulting sugarcane bagasse liquefaction polyol resin is denoted as H-1.
[0054] Adhesive compounding: Take 60 parts of H-1, 20 parts of C-1, 10 parts of epoxidized soybean oil, and 10 parts of deionized water, mix and stir evenly, adjust the pH to 8.0, and the adhesive is obtained, which is denoted as H-2.
[0055] Comparative Example 6: Comparison of different adhesive formulations Pretreatment of eucalyptus bark raw materials: Same as in Example 1.
[0056] Preparation of eucalyptus bark liquefied polyol resin: Same as in Example 1, the liquefied resin is denoted as A-1.
[0057] Preparation of carboxymethylated modified sugarcane pith: Same as in Example 1, the modified sugarcane pith is denoted as C-1.
[0058] Adhesive compounding: Take 40 parts of A-1, 40 parts of C-1, 10 parts of epoxidized soybean oil, and 10 parts of deionized water, mix and stir evenly, adjust the pH to 8.0, and the adhesive is obtained, which is denoted as I-1.
[0059] Comparative Example 7: A control using an inorganic acid (sulfuric acid) instead of p-toluenesulfonic acid as a catalyst. Pretreatment of eucalyptus bark raw materials: Same as in Example 1.
[0060] Preparation of eucalyptus bark liquefied polyol resin: A PEG-400 / glycerol mixed solvent (mass ratio 4:1) was used, with concentrated sulfuric acid (98% mass concentration) as the catalyst, at a dosage of 2.0% of the polyol solvent mass. The liquefaction temperature was 170℃, and the liquefaction time was 2.5 hours. Cooling: Same as in Example 1 (two-stage programmed cooling). The remaining operations were the same as in Example 1, and the resulting liquefied resin was designated J-1.
[0061] Adhesive compounding: Same as in Example 1 (J-1 60 parts, C-1 20 parts, epoxidized soybean oil 10 parts, water 10 parts, pH 8.0), adhesive is designated as J-2.
[0062] Test methods and performance evaluation The bio-based adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were used to press three-layer poplar plywood. The poplar veneers had dimensions of 400mm × 400mm × 1.5mm and a moisture content of 8%–10%. The adhesive application rate was 180g / m². 2 (Double-sided) After applying adhesive, allow to stand for 5 minutes, then hot-press at 120℃ for 5 minutes under 1.0MPa pressure. After standing for 24 hours, test the bonding strength and formaldehyde emission of the plywood according to GB / T 17657-2013 "Test Methods for Physical and Chemical Properties of Wood-based Panels and Decorative Wood-based Panels".
[0063] Dry bond strength: The dry bond strength of the specimen is measured directly after equilibration at (23±2)℃ and (50±5)% relative humidity for 7 days without immersion in water.
[0064] Wet bonding strength test: The specimen size was 100mm×25mm. After sawing, it was immersed in water at (63±3)℃ for 3 hours. After being taken out, it was cooled to room temperature for 10 minutes. The shear strength test was carried out on a universal testing machine with a loading speed of 10mm / min. The failure load was recorded. Ten specimens were tested for each sample, and the arithmetic mean was taken.
[0065] Formaldehyde emission measurement: using 1m 3Climate chamber method, temperature (23±0.5)℃, relative humidity (50±5)%, air exchange rate 1.0 times / hour, specimen exposure area 1.0m² 2 The sampling period was 7 days, and the tests were conducted according to Clause 4.60 of GB / T 17657-2013. In addition, to meet the requirements for Class I plywood, a boiling water immersion peel test was added: the specimen size was 75mm×75mm, immersed in boiling water for 4 hours, dried in a drying oven at (60±3)℃ for 20 hours, and then immersed for another 4 hours. The length of the adhesive layer delamination was observed, and the maximum value was taken as the delamination length of the sample.
[0066] Solid content determination: Weigh about 2g of sample into an aluminum foil dish, dry in an oven at 120℃ for 2 hours, weigh the residue, and calculate the solid content (residue mass / sample mass × 100%).
[0067] Liquefaction rate determination: After the liquefaction reaction is completed, the reaction mixture is cooled to room temperature, filtered through a 100-mesh filter, and the unreacted residue is collected and dried in an oven at 105℃ to constant weight, and then weighed. The liquefaction rate is calculated according to the following formula: Liquefaction rate (%) = (1 - dry weight of residue / amount of eucalyptus bark powder) × 100%.
[0068] Hydroxyl value (mgKOH / g): determined by phthalic anhydride-pyridine method.
[0069] The results of adhesive performance tests for each embodiment are summarized in the table below.
[0070] Table 1 Performance test results of the adhesives in the examples and comparative examples The bond strengths of Examples 1 to 3 were 1.13 MPa, 1.05 MPa, and 0.96 MPa, respectively, all meeting the requirement of ≥0.7 MPa for Class II plywood as specified in GB / T9846-2015, and significantly superior to Comparative Examples 1 to 7. Example 1 exhibited a bond strength as high as 1.13 MPa, a 34.5% increase compared to 0.84 MPa in Comparative Example 1, which is closest to the prior art, and a 121.6% increase compared to Comparative Example 2, which did not use modified sugarcane pith. Formaldehyde emissions from all three examples were undetectable (detection limit less than 0.1 mg / L), meeting the ENF standard. In the boiling water immersion peel test, the delamination length of the adhesive layer in Example 1 was only 0.6 mm, far less than the 5.6 mm in Comparative Example 1, demonstrating excellent water resistance.
[0071] Comparison with existing technology (Comparative Example 1). Comparative Example 1 represents the typical technical route of existing eucalyptus bark-based adhesives—phenol is liquefied and then polycondensed with formaldehyde to prepare phenolic resin. The bonding strength of this technology is 0.84 MPa, and the formaldehyde release is 1.5 mg / L, which belongs to the E2 level and cannot meet the formaldehyde-free environmental protection requirements. The bonding strength of Example 1 of this invention reaches 1.13 MPa, which is 34.5% higher than that; the formaldehyde release is undetectable, solving the formaldehyde pollution problem; the peeling length after boiling water immersion is reduced from 5.6 mm to 0.6 mm, and the water resistance is significantly improved. The core reason for this difference in effect is that this invention uses polyol instead of phenol as liquefaction agent, and epoxidized soybean oil instead of formaldehyde as crosslinking agent. At the same time, carboxymethylated modified sucrose pith is introduced as an active reinforcing component, forming a board-adhesive-surface synergistic system, avoiding the use of toxic and harmful substances from the source.
[0072] Compared with Comparative Example 2, which did not use modified sugarcane pith, Comparative Example 2 used the same PEG / glycerol liquefaction system and epoxidized soybean oil crosslinking system, but did not add any form of sugarcane pith. Its bond strength was only 0.51 MPa, and it completely peeled off after boiling water immersion, failing to meet national standards. Comparative Example 2 lacked the dual effects of "skeleton reinforcement" and "active crosslinking" of modified sugarcane pith—carboxymethylated modified sugarcane pith is rich in carboxymethyl functional groups, which can form a three-dimensional crosslinking network with the hydroxyl groups of liquefied polyol resin and the epoxy groups of epoxidized soybean oil. At the same time, the physical filling effect of sugarcane pith fibers enhances the mechanical properties of the adhesive layer. The bond strength of Example 1 of this invention is 121.6% higher than that of Comparative Example 2, proving that the introduction of carboxymethylated modified sugarcane pith is a key technical means to improve bond strength.
[0073] Compared with Comparative Example 3, which used unmodified sugarcane pith, Comparative Example 3, which used unmodified sugarcane pith instead of carboxymethylated sugarcane pith, had a bonding strength of only 0.58 MPa, a delamination length of up to 8.9 mm after boiling water immersion, and poor water resistance. Unmodified sugarcane pith can only function as a physical filler and cannot participate in chemical cross-linking; therefore, its bonding strength is much lower than the 1.13 MPa of Example 1 of this invention. This difference demonstrates the necessity of the carboxymethylation modification step—introducing carboxymethyl functional groups to upgrade sugarcane pith from an inert filler to an active cross-linking component.
[0074] Verification of liquefaction temperature and time parameter optimization experiments (Comparative Example 4). Comparative Example 4 used liquefaction at 130℃ (below the lower limit of 140℃), and the liquefaction time was extended to 3.5 hours. The liquefaction rate decreased to 78.4%, and the hydroxyl value of the liquefaction product decreased to 268 mgKOH / g. The adhesive bond strength was only 0.63 MPa, lower than the national standard of 0.7 MPa. The reason is that the liquefaction temperature was too low, resulting in insufficient degradation of the high lignin content (approximately 45%) in the eucalyptus bark, and the active hydroxyl groups of the liquefaction product were insufficient to form sufficient cross-links with epoxidized soybean oil.
[0075] Comparative Example 5 used bagasse powder (the pith removed) instead of eucalyptus bark as the liquefaction raw material. The chemical composition of bagasse powder differs fundamentally from that of eucalyptus bark—bagasse powder has a high cellulose content (approximately 50%) and a lignin content of only about 20%, contrasting sharply with the high lignin content of eucalyptus bark (up to 45%). The adhesive bond strength of Comparative Example 5 was only 0.55 MPa, far lower than the 1.13 MPa of Example 1. This result indicates that the liquefaction step of this invention is optimized for use with eucalyptus bark raw materials with high lignin content.
[0076] Validation of component ratio optimization (Comparative Example 6). In Comparative Example 6, the amount of carboxymethylated modified sugarcane pith exceeded the upper limit of 10-30 parts, reaching 40 parts. Although formaldehyde was not detected and the bonding strength of 0.82 MPa met the national standard, the application viscosity was as high as 1850 mPa·s, significantly exceeding the suitable window of 800-1500 mPa·s for easy application, resulting in a significant decrease in process operability. In Comparative Example 2, the bonding strength did not meet the standard when the amount of modified sugarcane pith was 0 parts.
[0077] Validation of the optimal catalyst selection experiment (Comparative Example 7). Comparative Example 7 used concentrated sulfuric acid instead of p-toluenesulfonic acid as the catalyst. Under the same liquefaction temperature (170℃) and time (2.5 hours), the liquefaction rate was only 83.6%, lower than the 88.2% of Example 1. The acid value of the liquefied product (15.8 mgKOH / g) was higher than that of Example 1 (10.2 mgKOH / g), resulting in a decrease in the bonding strength to 0.88 MPa. Concentrated sulfuric acid easily initiates etherification and dehydration side reactions in the polyol liquefaction system, and excessive acidity leads to the consumption of some active hydroxyl groups. Furthermore, the increased acid value of the reaction system inhibits the ring-opening crosslinking of epoxidized soybean oil, which is a significant reason for the decrease in bonding strength.
[0078] From Example 1 to Example 3, the amount of carboxymethylated modified sugarcane pith was increased from 20 parts to 25 parts and then decreased to 15 parts, with corresponding adjustments to the liquefaction temperature and PEG / glycerol ratio. Example 1 (20 parts C-1, 170℃, PEG:glycerol = 4:1) achieved the highest bond strength (1.13 MPa), indicating that the synergistic effect between the modified sugarcane pith and the liquefaction resin was optimal under this ratio. Example 3 (15 parts C-3, 175℃, PEG:glycerol = 4.2:1) had a bond strength of 0.96 MPa, slightly lower than Example 1, possibly due to a lower hydroxyl value caused by a higher liquefaction temperature. All three examples met the core requirements of a bond strength ≥ 0.7 MPa and undetectable free formaldehyde.
[0079] In summary, this invention successfully solves the technical challenge of preparing high-performance bio-based adhesives using eucalyptus bark and sugarcane pith as organic raw materials without the use of phenol and formaldehyde, achieving the following technical effects: a maximum bonding strength of 1.13 MPa, meeting the technical requirements for Class II plywood in GB / T 9846-2015; a peeling length after boiling water immersion of only 0.6 mm, far superior to the 5.6 mm of existing technologies; undetectable formaldehyde release, meeting the ENF standard; and the synergistic utilization of eucalyptus bark and sugarcane pith during the preparation process, with a liquefaction rate ≥88.2%. This invention breaks through the existing technical route of phenol liquefaction + formaldehyde polycondensation in eucalyptus bark-based adhesives, not only completely eliminating the introduction of harmful substances such as formaldehyde, but also improving the bonding strength by 34.5% compared to existing aldehyde-containing technologies. By upgrading sugarcane pith from an inert filler to an active cross-linking reinforcing component, the goal of self-disposal of waste is achieved, providing a practical and feasible technical path for the high-value utilization of characteristic biomass resources in Guangxi.
[0080] Example 4 (Stabilization Treatment) This embodiment adds a stabilization treatment step to Example 1 to verify the effect of stabilization treatment on the storage stability of eucalyptus bark liquefied polyol resin.
[0081] Pretreatment of eucalyptus bark raw material: Same as in Example 1. Take eucalyptus bark, dry it at 70°C to a moisture content of 5%, pulverize it through an 80-mesh sieve, extract it by reflux extraction with benzene-ethanol (2:1, v / v) at 70°C for 3 hours, vacuum dry the filter residue at 60°C, and then pulverize it through a 120-mesh sieve to obtain pretreated eucalyptus bark powder.
[0082] Preparation of liquefied polyol resin from eucalyptus bark (unstabilized): 300 g of a mixed solvent of PEG-400 and glycerol (mass ratio 4:1) was added to a 500 mL four-necked flask. 6 g of p-toluenesulfonic acid (2.0% of the solvent mass) was added and stirred until dissolved. 100 g of pretreated eucalyptus bark powder was added, and the mixture was heated to 170 °C at 5 °C / min and reacted at this temperature for 2.5 hours. After the reaction was complete, the temperature was lowered according to a program (2 °C / min to 100 °C, then 4 °C / min to room temperature) to obtain the liquefied resin, denoted as A-4-raw (unstabilized).
[0083] Stabilization treatment: Calcium carbonate (nanoscale, average particle size 100 nm) and glycerol were mixed at a mass ratio of 1:1 and placed in a planetary ball mill. The mixture was ground at 300 r / min for 45 minutes to obtain a calcium carbonate-glycerol dispersion slurry. This slurry was added to the above A-4-raw, making the net addition of calcium carbonate 1.0% of the mass of the liquefied resin. The mixture was mechanically stirred at 45°C for 45 minutes, then vacuum filtered through a 200-mesh filter cloth to remove solid residue, yielding a stabilized eucalyptus bark liquefied polyol resin, denoted as A-4-stab.
[0084] Preparation of carboxymethylated modified sugarcane pith: Same as in Example 1, yielding C-1.
[0085] Adhesive compounding: Take 60 parts of A-4-stab, 20 parts of C-1, 10 parts of epoxidized soybean oil (epoxidation value 6.5%), and 10 parts of deionized water, disperse at high speed for 15 minutes, and adjust the pH to 8.0 with 10% NaOH to obtain the adhesive, which is denoted as G-4.
[0086] Control sample: To compare the stabilization effect, unstabilized A-4-raw was also mixed in the same proportion to obtain adhesive G-4-raw (all other components were exactly the same).
[0087] Comparative Example 8 (no calcium carbonate used, stored naturally only) This comparative example is used to verify the performance of unstabilized liquefied resin during storage.
[0088] Take A-4-raw (untreated) from Example 4 and store it in a sealed container at 25℃±2℃ in the dark for 90 days. Samples were taken on days 0, 30, 60, and 90, and adhesives were prepared according to the compounding method of Example 4 (with the same proportions as G-4-raw). Plywood was pressed and the bond strength was tested. Simultaneously, the acid value, viscosity, and appearance changes of the liquefied resin were monitored.
[0089] Comparative Example 9 (micron-sized calcium carbonate powder was added directly, without ball milling) This comparative example is used to verify the stabilizing effect of directly adding ordinary micron-sized calcium carbonate (without pre-dispersion).
[0090] Take A-4-raw (same as in Example 4), add 1.0% (by weight of the liquefied resin) of industrial-grade heavy calcium carbonate powder (average particle size 15 μm, without any pretreatment), mechanically stir at 45°C for 45 minutes, and vacuum filter through a 200-mesh filter cloth to obtain the treated liquefied resin, denoted as A-9-stab. Adhesive G-9 was prepared according to Example 4. Its storage stability was tested.
[0091] Comparative Example 10 (Calcium oxide was added instead of calcium carbonate) This comparative example is used to verify the applicability of other alkaline solids (calcium oxide).
[0092] Take A-4-raw (same as in Example 4), add 0.5% (by weight of the liquefied resin) of calcium oxide (CaO, analytical grade, powder), stir at 45°C for 45 minutes, filter (the solution becomes noticeably turbid, and some gel-like substances form), and after barely filtering, obtain liquefied resin A-10-stab. Reconstitute according to Example 4 (but A-10-stab has an abnormally high viscosity and cannot be uniformly coated), and designate it as G-10.
[0093] Effect Experiment The liquefied resins of Example 4 (A-4-stab), Comparative Example 8 (A-4-raw), Comparative Example 9 (A-9-stab), and Comparative Example 10 (A-10-stab) were sampled at 0 days, 30 days, 60 days, and 90 days, respectively, and the following indicators were tested: Acid value (mgKOH / g): determined by acid-base titration: weigh an appropriate amount of sample and dissolve it in an acetone-water mixed solvent, using phenolphthalein as an indicator, and titrate with a potassium hydroxide-ethanol standard titration solution.
[0094] Viscosity (25℃, mPa·s): Measured using a rotational viscometer.
[0095] Appearance and color: Visual observation (light yellow → yellow → reddish brown → dark brown).
[0096] Bond strength: Liquefied resin stored for different times was mixed with the same ratio (60 parts liquefied resin, 20 parts C-1, 10 parts epoxidized soybean oil, 10 parts water, pH 8.0) to prepare an adhesive, which was then pressed into poplar three-layer plywood (under the same conditions as in Example 1) and the wet bond strength (Class II impregnation peel) was tested.
[0097] Hydroxyl value (mgKOH / g): determined by phthalic anhydride-pyridine method (only 0 days and 90 days were measured).
[0098] Experimental results Table 2. Changes in storage stability and bonding strength of liquefied resin under different treatment methods. Note: The calcium oxide treatment in Comparative Example 10 caused the liquefied resin to gel rapidly (CaO reacts with water to generate Ca(OH)2, and the strong alkalinity caused pre-crosslinking of the epoxidized soybean oil), rendering it unusable. "—" in the table indicates that the test was not performed or could not be performed.
[0099] Results Analysis Comparative Example 8, untreated A-4-raw, showed the following changes after 90 days of storage: acid value increased from 11.2 mgKOH / g to 20.1 mgKOH / g (an increase of 79%), viscosity surged from 1050 mPa·s to 2850 mPa·s (an increase of 171%), color changed from light yellow to orange-red, and hydroxyl value decreased from 312 to 268 mgKOH / g (a decrease of 14%). Correspondingly, the bonding strength decreased, falling below the national standard of 0.7 MPa. This indicates that residual p-toluenesulfonic acid continued to catalyze side reactions, leading to severe deterioration of the liquefied resin.
[0100] Comparative Example 9, after treatment with ordinary micronized calcium carbonate, had an initial acid value reduced to 6.5 mgKOH / g (still significantly higher than the 1.8 mgKOH / g in Example 4). After 90 days of storage, the acid value increased to 9.8 mgKOH / g, the viscosity increased from 1120 to 1680 mPa·s (an increase of 50%), and the bond strength decreased from 1.05 MPa to 0.87 MPa (still decreasing). This is because the micronized calcium carbonate particles are large and have a small specific surface area, failing to fully neutralize the residual acid. Furthermore, it was not pre-dispersed with glycerol, resulting in some calcium carbonate agglomeration that failed to participate in the reaction, leaving a small amount of acid residue after filtration.
[0101] In Comparative Example 10, calcium oxide reacted with water to form strongly alkaline calcium hydroxide, causing the epoxidized soybean oil in the liquefied resin (even before the compounding stage) to undergo violent ring-opening crosslinking, resulting in a gelled system that was completely unusable. This demonstrates that strongly alkaline solids are unsuitable for this system.
[0102] In Example 4, nano-calcium carbonate (100 nm) was pre-dispersed by ball milling with glycerol and then added, reducing the initial acid value to 1.8 mg KOH / g (residual acid was almost completely neutralized). After 90 days of storage, the acid value only slightly increased to 2.3 mg KOH / g, the viscosity increased from 1080 to 1180 mPa·s (an increase of only 9.3%), the hydroxyl value decreased from 310 to 301 mg KOH / g (a decrease of 2.9%), and the color remained almost unchanged. The bond strength decreased from 1.11 MPa to 1.08 MPa, but remained at a very high level (>1.0 MPa). This demonstrates that the stabilization treatment completely eliminated the catalytic effect of residual acid, giving the liquefied resin excellent long-term storage stability.
[0103] In Examples 1 to 3, the liquefied resin was not stabilized and was used as soon as possible (usually within 1 week) after preparation. In Example 4, by adding a stabilization step, the shelf life of the liquefied resin was extended from less than 1 month to at least 3 months, and the stabilization treatment had little impact on the bonding strength.
[0104] Example 4 demonstrates that stabilization treatment (nano-calcium carbonate, glycerol ball milling pre-dispersion, neutralization, and filtration) can reduce the initial acid value of the liquefied resin from 11.2 mgKOH / g to 1.8 mgKOH / g (residual acid removal efficiency of 84%); after 90 days of storage at room temperature, the acid value of the liquefied resin only increases to 2.3 mgKOH / g, the viscosity increase rate is <10%, and the hydroxyl value retention rate is >97%. The adhesive prepared using liquefied resin stored for 90 days still maintains a bonding strength of 1.08 MPa (untreated liquefied resin only has 0.52 MPa after 90 days), which is significantly better than the treatment method of directly using micron-sized calcium carbonate or calcium oxide.
[0105] Example 5 (Preparation of bamboo-wood composite board) The application of the bio-based adhesive prepared according to the present invention in the preparation of bamboo-wood composite boards includes: I. Raw Material Processing Eucalyptus fiber core layer: Processing residues of eucalyptus (Eucalyptus urophylla) from Guangxi region are crushed, dried, and sieved to obtain eucalyptus fiber with a moisture content controlled at 8%–10%, for later use. Based on the oven-dry weight of the fiber, 15% unmodified sugarcane pith (same as F-2 in Comparative Example 3, particle size 80 mesh) is added and mixed evenly to serve as the core layer filler.
[0106] Bamboo reinforcement layer: Take 3-4 year old moso bamboo (Phyllostachys pubescens), remove the outer green and inner yellow parts, split it into strips 10-15mm wide, and roll it into bamboo bundles about 5mm thick. Control the moisture content at 8%-10% and set aside. The surface of the bamboo bundles to be glued (the surface in contact with the eucalyptus core layer) should remain in its original, untreated state (without mechanical sanding).
[0107] Bio-based adhesive stock solution: Prepared according to the method in Example 1, namely A-1 (60 parts liquefied resin), C-1 (20 parts carboxymethylated modified sucrose pith), 10 parts epoxidized soybean oil (epoxidation value 6.5%), and 10 parts deionized water. The pH was adjusted to 8.0 with a 10% sodium hydroxide aqueous solution, and this solution is designated as G-1. This adhesive should be used within 2 hours of preparation.
[0108] II. Bamboo Surface Pretreatment (Steps A and B) Preparation of bamboo surface pretreatment agent: Take 6g of carboxymethylated modified sugarcane pith (C-1), add it to 180mL of deionized water, stir in a 60℃ water bath, add 12g of glycerol, adjust the pH to 8.5 with 10% sodium hydroxide aqueous solution, add water to the total volume of 200mL, and obtain a mixed aqueous dispersion with a carboxymethylated sugarcane pith mass concentration of 3.0% and a glycerol mass concentration of 6.0%. Stir evenly to obtain the pretreatment agent, denoted as P-1.
[0109] Lay the bamboo curtain flat with the glued side facing up, and spray P-1 evenly with a spray gun at a rate of 45g / m². 2 (Based on the unfolded area of the bamboo bundle curtain). The bamboo bundle curtain is then placed in a forced-air drying oven and dried at 70°C for 4 minutes to form a carboxymethylated sucrose pith porous coating on the bamboo surface. This pretreated bamboo reinforcement layer is denoted as Bamboo-P.
[0110] III. Eucalyptus Surface Sealing (Steps CD) Preparation of eucalyptus surface sealant: Take the above G-1 adhesive stock solution and anhydrous ethanol at a volume ratio of 1:0.8, mix them, stir evenly, and obtain the sealant, which is denoted as S-1.
[0111] The eucalyptus fiber core layer is laid into a board blank (300mm×300mm×10mm, density 0.65g / cm³). 3 S-1 is sprayed on both the upper and lower surfaces, with a coating amount of 30g / m². 2 (Single-sided). After spraying, allow the ethanol to evaporate naturally at room temperature for 3 minutes, which partially seals the pores on the eucalyptus surface, resulting in a sealed eucalyptus core layer, denoted as Eucalyptus-S.
[0112] IV. Glue application and preform assembly (Step EG) Take the G-1 adhesive concentrate and apply it to the following areas using a scraper: The pretreated bamboo reinforcement layer (Bamboo-P) is applied to the bonding surface with an adhesive application rate of 140 g / m² on one side. 2 ; The top and bottom surfaces of the sealed eucalyptus core layer (Eucalyptus-S) are coated with adhesive at a rate of 140 g / m² per side. 2 .
[0113] Assemble the blanks in the following order: "bamboo reinforcement layer (top) - eucalyptus core layer - bamboo reinforcement layer (bottom)" to form a three-layer structure blank. The total thickness is approximately 20mm (10mm core layer + 5mm bamboo layers + adhesive layer).
[0114] V. Hot pressing and pressure holding cooling (step H) The slab is placed in a hot press, and the hot pressing parameters are set as follows: temperature: 140℃; pressure: 1.5 MPa; hot pressing time: 10 minutes. After hot pressing, the pressure is kept constant, and the cooling system is started to reduce the temperature of the hot press plate to 70℃ (the center temperature of the slab is about 65℃) at a rate of 5℃ / min. Then the pressure is released, and the slab is removed. The resulting bamboo-wood composite board is designated Panel-5.
[0115] VI. Adding accelerators to the pretreatment agent To verify the effect of the accelerator, another batch of bamboo pretreatment agent was prepared: based on the above P-1, 0.3% of 2-ethyl-4-methylimidazolium (EMI-24) by mass of carboxymethylated sucrose pith was added, stirred and dissolved, and this was designated P-2. The remaining steps were exactly the same (bamboo was sprayed with P-2 and then dried, eucalyptus wood was sealed as before, and the gluing, assembly, hot pressing and pressure holding cooling were as before), resulting in a bamboo-wood composite board, designated Panel-5-P.
[0116] Comparative Example 11 (no bamboo surface pretreatment, no eucalyptus surface sealing) Using untreated bamboo blinds and unsealed eucalyptus core layers directly, with the same glue application amount (140 g / m²) as in Example 5. 2The same hot-pressing conditions (140℃, 1.5MPa, 10 minutes) were applied, but the pressure was immediately released after hot pressing (without holding pressure and cooling). This yielded the composite panel Panel-11.
[0117] Comparative Example 12 (bamboo pretreatment only, no eucalyptus wood sealing) The bamboo pretreatment is the same as in Example 5 (using P-1), but the eucalyptus core layer is not sealed. Pressure is released immediately after hot pressing (no pressure holding or cooling). Panel-12 is obtained.
[0118] Comparative Example 13 (Eucalyptus wood only, no bamboo pretreatment) The eucalyptus wood was sealed as in Example 5 (using S-1), but the bamboo was not pretreated. Pressure was released immediately after hot pressing. This yielded Panel-13.
[0119] Comparative Example 14 (no pressure holding cooling, otherwise the same as Example 5) All the pretreatment and sealing steps of Example 5 were used (P-1 for bamboo, S-1 for eucalyptus), but the pressure was immediately released after hot pressing (without holding pressure and cooling). Panel-14 was obtained.
[0120] Comparative Example 15 Commercially available phenolic resin adhesive (PF resin, solid content 48%, viscosity 800 mPa·s, free formaldehyde 0.3%) was used. Neither bamboo nor eucalyptus underwent any pretreatment or sealing; the adhesive was applied directly (150 g / m² on one side). 2 After assembly, the blanks are hot-pressed (140℃, 1.5MPa, 10 minutes), and the pressure is released directly after hot pressing. This yields the composite panel Panel-15.
[0121] Effect Experiment Tests were conducted in accordance with GB / T 17657-2013 and LY / T 2220-2013.
[0122] Wet bond strength: Ten specimens (50mm×50mm) were cut from each composite board, immersed in water at (63±3)℃ for 3 hours, cooled to room temperature for 10 minutes, and then tested for shear strength using a universal testing machine (loading speed 10mm / min). The bamboo-wood interface and the wood-wood interface (inside the core layer) were tested separately.
[0123] Boiling water immersion peeling: The specimen is 75mm×75mm. It is immersed in boiling water for 4 hours, dried at 60℃ for 20 hours, and then immersed in boiling water for 4 hours. The length of delamination at the bamboo-wood interface is measured (take the maximum value).
[0124] Thickness rebound rate: Measure the thickness of the slab after hot pressing (immediately after depressurization) and the thickness after 24 hours of storage, and calculate the thickness rebound rate = (24-hour thickness - initial thickness) / initial thickness × 100%.
[0125] Surface defect rate: Observe whether there are bubbles or delamination on the surface of the board, and count the percentage of defective area.
[0126] Formaldehyde emission: using 1m 3 Climate chamber method (same as Example 1).
[0127] The experimental results are as follows: Table 3 Comparison of Plywood Performance Results Analysis Panel-11, without any treatment, had a bamboo-wood interface bonding strength of only 0.47 MPa (<0.7 MPa), delamination of 7.8 mm after boiling water immersion, a thickness resilience of 7.0%, and obvious surface blistering. This was because the hydrophobic surface of bamboo prevented the adhesive from effectively wetting the wood, while the porous nature of eucalyptus wood excessively absorbed the adhesive, resulting in insufficient adhesive at the bamboo-wood interface. Panel-5, after bamboo activation and eucalyptus sealing, showed a bamboo-wood interface strength increased to 1.17 MPa, with delamination of only 0.2 mm, a resilience of 2.2%, and no defects.
[0128] Panel-12, with only bamboo pretreatment: The bamboo-wood interface strength increased to 0.84 MPa (barely meeting the standard), but the eucalyptus was not sealed, and the adhesive was still excessively absorbed, resulting in 3.3 mm of delamination and a resilience rate of 5.4%, indicating remaining defects. Panel-13, with only eucalyptus sealing: The bamboo-wood interface strength was only 0.61 MPa (not meeting the standard) because the bamboo was not activated. Neither of these treatments is as good as the combined treatment.
[0129] Panel-14, without pressure-holding cooling, despite pretreatment and sealing, experienced immediate pressure release after hot pressing. This resulted in the bamboo's rebound stress damaging the adhesive layer. The bamboo-wood interface strength decreased from 1.17 MPa to 0.95 MPa, delamination increased from 0.2 mm to 1.6 mm, and the resilience rate increased from 2.2% to 4.6%. This demonstrates that pressure-holding cooling, allowing the adhesive layer to fully cure under pressure before pressure release, effectively resists rebound stress.
[0130] Adding 0.3% EMI-24 to the bamboo pretreatment agent increased the bamboo-wood interface bonding strength to 1.31 MPa (a 12% increase), reduced delamination after boiling water impregnation to 0.1 mm, and decreased the resilience to 1.6%. This is because the accelerator directionally catalyzes the early curing of the bamboo-adhesive interface, forming a high-strength anchoring layer in the early stages of hot pressing to resist rebound stress. Simultaneously, the accelerator is limited to the bamboo surface and does not affect the adhesive's pot life or toughness.
[0131] Bamboo-wood composite boards prepared with conventional phenolic resin have a bamboo-wood interface strength of 0.91 MPa, a delamination length of 3.6 mm, a resilience of 4.0%, and a formaldehyde emission of 0.28 mg / L (E1 grade). The Panel-5 of this invention is not only formaldehyde-free, but also exhibits a 28% increase in strength, a 94% reduction in delamination length, and a 45% reduction in resilience. Panel-5-P demonstrates even greater advantages.
[0132] In summary, the combination of the bamboo surface pretreatment agent (carboxymethylated sucrose pith mass concentration 2%–5%, glycerol 5%–10%, pH 8.0–9.0) and the eucalyptus surface sealant (adhesive stock solution and ethanol volume ratio 1:0.5–1:1) described in Example 5 increased the bamboo-wood interface bonding strength from 0.47 MPa to 1.17 MPa. After hot pressing, the pressure was maintained and cooled to 60–80°C at a cooling rate of 3–8°C / min, reducing the thickness resilience from 4.6% to 2.2% and the delamination length from 1.6 mm to 0.2 mm. The addition of 0.1%–0.5% (by mass) of 2-ethyl-4-methylimidazolium to the pretreatment agent further increased the bamboo-wood interface strength to 1.31 MPa and reduced the resilience to 1.6%.
[0133] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. It can be applied to various fields suitable for the present invention. Further modifications can be readily implemented by those skilled in the art.
Claims
1. A method for preparing a bio-based adhesive using eucalyptus bark and sugarcane pith, characterized in that, Includes the following steps: Step 1: Mix dried and pulverized eucalyptus bark with polyol solvent and acidic catalyst, and react at 140℃~180℃ for 1~3 hours. After cooling, eucalyptus bark liquefaction polyol resin is obtained. Step 2: Mix the dried and pulverized sugarcane pith with sodium hydroxide aqueous solution and chloroacetic acid, and react at 50℃~70℃ for 1~3 hours. After neutralization, washing and drying, carboxymethylated modified sugarcane pith is obtained. Step 3: By weight, take 40-80 parts of the eucalyptus bark liquefied polyol resin obtained in Step 1, 10-30 parts of the carboxymethylated modified sugarcane pith obtained in Step 2, 5-20 parts of epoxidized soybean oil, and 5-20 parts of water, and mix them evenly. Step 4: Adjust the pH of the mixture obtained in Step 3 to 7.5-9.0 with an alkaline substance to obtain the bio-based adhesive.
2. The method according to claim 1, characterized in that, In step one, the polyol solvent is a mixture of polyethylene glycol and glycerol, wherein the mass ratio of polyethylene glycol to glycerol is 3.5:1 to 4.5:1, and the average molecular weight of polyethylene glycol is 300 to 600; the acidic catalyst is p-toluenesulfonic acid, and the amount used is 1% to 4% of the mass of the polyol solvent; the reaction temperature is 170℃, and the time is 2.0 to 2.5 hours; the cooling is a programmed cooling: first, the temperature is reduced from 170℃ to 100℃ at a rate of 1 to 3℃ / min, and then the temperature is reduced from 100℃ to room temperature at a rate of 3 to 5℃ / min.
3. The method according to claim 1, characterized in that, Before step one, the eucalyptus bark is pretreated as follows: the eucalyptus bark is dried at 60℃~80℃ to a moisture content of 3%~8%, pulverized to 60~100 mesh, then extracted by reflux extraction with a benzene-ethanol mixed solvent at 65℃~75℃ for 2~4 hours, filtered, and the filter residue is dried again at 60℃~80℃ to constant weight, and finally pulverized to pass through an 80~200 mesh sieve to obtain dried and pulverized eucalyptus bark.
4. The method according to claim 1, characterized in that, In step two, the mass ratio of dried and pulverized sugarcane pith, sodium hydroxide, and chloroacetic acid is 100:5-15:10-20; neutralization is achieved by adjusting the pH to 6.5-7.0 with dilute hydrochloric acid or dilute sulfuric acid; washing is performed 2-4 times with deionized water or ethanol; and drying is performed under vacuum at 50℃-70℃ until constant weight.
5. The method according to claim 1, characterized in that, In step three, the epoxy value of the epoxidized soybean oil is 6.0% to 7.0%.
6. The method according to claim 1, characterized in that, In step four, the alkaline substance is an aqueous solution of sodium hydroxide or sodium carbonate, with a mass concentration of 5% to 20%.
7. The method according to claim 1, characterized in that, Step one is followed by a stabilization treatment: 0.5% to 2% of calcium carbonate powder (nano-sized calcium carbonate with an average particle size of 50 to 200 nm) is added to the eucalyptus bark liquefied polyol resin. The calcium carbonate powder is mixed with glycerol at a mass ratio of 1:0.5 to 1:2 and then ground in a ball mill at 200 to 400 r / min for 30 to 60 minutes to form a slurry before being added. The mixture is stirred at 40°C to 50°C for 30 to 60 minutes, and then filtered to remove solid residues to obtain the stabilized eucalyptus bark liquefied polyol resin.
8. The application of a bio-based adhesive prepared by the method according to any one of claims 1 to 7 in the preparation of bamboo-wood composite panels, characterized in that, Includes the following steps: Step A: Prepare a bamboo surface pretreatment agent. The pretreatment agent is a mixed aqueous dispersion of carboxymethylated sucrose pith and glycerol, wherein the mass concentration of carboxymethylated sucrose pith is 2% to 5% and the mass concentration of glycerol is 5% to 10%. Adjust the pH to 8.0 to 9.0 with sodium hydroxide. Step B: Impregnate or spray the surface of the bamboo reinforcement layer to be glued with a pretreatment agent, and dry it at 60℃~80℃ for 3~5 minutes to form a carboxymethylated sucrose pith coating on the bamboo surface, thus obtaining the pretreated bamboo reinforcement layer. Step C: Prepare a eucalyptus surface sealant, wherein the sealant is a diluted solution of the bio-based adhesive stock solution according to any one of claims 1 to 7 and ethanol at a volume ratio of 1:0.5 to 1:1; Step D: Spray the sealant onto the upper and lower surfaces of the eucalyptus fiber core layer, with a spraying amount of 20-40 g / m². 2 The ethanol will evaporate naturally in 2-4 minutes; Step E: Prepare a bio-based adhesive stock solution using the method described in any one of claims 1 to 7, for later use; Step F: Apply the bio-based adhesive concentrate to the pretreated bamboo reinforcement layer and the upper and lower surfaces of the sealed eucalyptus fiber core layer, with a single-sided application rate of 120-150 g / m². 2 ; Step G: Assemble the blanks in the order of eucalyptus fiber core layer in the middle and bamboo reinforcement layer on both sides to form a board blank; Step H: Place the slab in a hot press and hot press it for 8 to 12 minutes at 130℃~150℃ and 1.2~1.8MPa. After cooling, the bamboo-wood composite board is obtained.
9. The application according to claim 8, characterized in that, After hot pressing in step H is completed, the pressure is maintained to cool the slab to 60℃~80℃ at a cooling rate of 3℃ / min~8℃ / min, and then the pressure is released and the slab is removed.
10. The application according to claim 8, characterized in that, The pretreatment agent described in step A also contains 0.1% to 0.5% of 2-ethyl-4-methylimidazole by mass of carboxymethylated sugarcane pith.
Citation Information
Patent Citations
A method for preparing eucalyptus bark powder modified phenolic resin wood adhesive
CN111961429B